Detection of serum FOXM1 and IGF2 in patients with ARDS and their correlation with disease and prognosis - Liu Chao; Zhang Shengrui; Zhang Weiwei; Wang Jinfeng (Open Medicine, 2024)
To investigate the relationship between the expression levels of serum forkhead box protein M1(FOXM1) and insulin-like growth factor 2 (IGF2) mRNA in patients with acute respiratory distress syndrome (ARDS) condition and prognosis.